Whipple's disease: a rare case of malabsorption. (5th March 2018) - Lopes, Ana; Santos, Ana Filipa; Alvarenga, Maria Joana; Mello e Silva, Alberto
Abstract : Whipple's disease is a chronic, rare, multisystemic, infectious entity, described for the first time in 1907. Its aetiological agent is the Gram-negative rod, Tropheryma whipplei, which was isolated for the first time in 2001 from a cardiac valve of a patient with endocarditis. We present the case of a 71-year-old man, who came into the emergency room complaining of anorexia, weakness, abdominal pain and diarrhoea with haematochezia and presented disseminated palpable purpuric lesions, predominantly in the lower limbs. The upper endoscopy showed a duodenal vasculitis and the biopsy of that location revealed aspects suggestive of Whipple's disease. We started him on antibiotics according to the recent orientations with progressive clinical and analytical improvement, although he developed an immune reconstitution syndrome, which lasted for 2 weeks.